Description of Entrepreneurial Interest in Culinary Management Training Graduates in Nagari Durian Gadang, Sijunjung District - Amelia Putri, Astri; Natsir, MHD (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the lack of skills of the Nagari Durian Gadang community, the high unemployment rate of the Durian Gadang community, and the lack of public knowledge about culinary procedures. Therefore, training was held in the culinary field to increase interest in entrepreneurship in the community and to reduce unemployment in Nagari Durian Gadang. This study aims to: (1) explain the description of interest in entrepreneurship based on the aspect of choosing activities based on one's own desires and the wishes of others, (2) explain the description of interest in entrepreneurship based on aspects of feelings of interest in entrepreneurship. , (3) explaining the description of interest in entrepreneurship based on aspects of the feeling of pleasure in entrepreneurship, and (4) explaining the description of interest in entrepreneurship based on the aspect of determining the choice of activities from one's own desires and the will of others, (5) explaining the description of interest in entrepreneurship based on the aspect of taking risks.This type of research is a quantitative approach to the type of descriptive analysis. The population in this study were 40 people. The sampling technique used cluster random sampling, a sample of 20 people. Data collection technique is a questionnaire. Data analysis techniques use percentages to see a picture of entrepreneurial interest.The results of the conclusions of this study indicate that (1) the interest in entrepreneurship in culinary training graduates at Nagari Durian Gadang based on the sub-variable makes the choice of activity categorized as good, (2) the interest in entrepreneurship in culinary training graduates in Nagari Durian Gadang based on the sub-variable feels interested in entrepreneurship categorized as good, (3) interest in entrepreneurship in culinary training graduates at Nagari Durian Gadang based on the sub-variable feels good about entrepreneurship is categorized as good, (4) interest in entrepreneurship in culinary training graduates at Nagari Durian Gadang based on the sub-variable desire to do entrepreneurship is categorized as good. (5) the interest in entrepreneurship in culinary training graduates at Nagari Durian Gadang based on the risk-taking sub-variable is categorized as good.Keywords: Interest in Entrepreneurship, Culinary Training.